Construction quality of school buildings using the Industrialised Building System (IBS) - Ali, Maisarah; Jaafar, Ab Nasir; Kamaruddin, Ibrahim; Abdul Rahman , Hamzah (Construction Research Institute of Malaysia, 2012)
One of the major problems in the Malaysian construction industry is the shortage of skilled labour. Due to this shortage, many contractors have resorted to employing semi-skilled and unskilled labourers thus resulting in poor workmanship in construction. To overcome this and its related problems, the Malaysian Government through the Construction Industry Development Board (CIDB) presently encouraged the IBS method of construction by the industry. With this initiative in place, it is expected that the quality of construction in buildings will be further improved. The aim of this study is to assess the quality of selected school buildings in Malaysia constructed using the Industrialised Building System (IBS) method of construction and comparing it with the quality of buildings constructed using conventional construction methods. This study involves the physical inspection of buildings, an analysis of the defect lists obtained from the relevant authorities and a questionnaire survey circulated to end users to obtain a feedback on their perception on the quality of the completed buildings. The results of this study demonstrate that the quality of IBS-constructed buildings had substantially better quality as compared to those constructed by the conventional methods. The result of the study together with numerous other studies on the IBS construction method would encourage the Malaysian construction players to increase the use of IBS in future construction projects. Keywords: Quality, Industrialised Building System, Conventional construction method, School buildings